Constraint analysis of dairy sector in North Eastern Region: A producers and consumers perspective - Singh, Ram; Chiphang, Singyala; Ajmer, Singh (Indian Journal of Dairy Science, 2021)
The paper made an attempt to examine the constraints faced by the dairy farmers and consumers of milk and milk products in the North East region (NER). Assam and Meghalaya were selected purposively as these states were the leading states in cattle population.Â  Primary data were collected randomly from 284 respondents of which 110 were dairy farmers and 174 were consumers.Garretâ€™s ranking technique was adopted to analyze the constraints faced by the stakeholders. The major constraints faced by the dairy farmers were the high cost of cattle feed and fodder, inadequate availability of green fodder, lack of organized set up for milk procurement and sale. For the consumers, the major constraints were adulteration, lack of desired quality and lack of quality control. Thus, efforts should be made from the government to take proper steps in regulating the prices for the feed and concentrates. Additionally, efforts to set up quality control centre at the block/cluster level so that they can monitor the quality regularly which will further enhance the quality of milk and milk products in order to create a win-win situation for both the stakeholders.